2009
DOI: 10.1097/bcr.0b013e3181b48102
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evidence for the Effects of Morphine on Posttraumatic Stress Disorder Symptoms in One- to Four-Year-Olds With Burns

Abstract: This study tested the hypothesis that very young children who received more morphine for acute burns would have larger decreases in posttraumatic symptoms 3 to 6 months later. This has never before been studied in very young children, despite the high frequency of burns and trauma in this age group. Seventy 12- to 48-month-old nonvented children with acute burns admitted to a major pediatric burn center and their parents participated. Parents were interviewed at three time points: during their child's hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(39 citation statements)
references
References 26 publications
2
37
0
Order By: Relevance
“…Our findings are in line with previous studies in injured populations that reported associations between morphine prescription and lower levels of PTSD symptoms or lower PTSD incidence in the months following injury [39][40][41][42][43]. Furthermore, they extend these previous findings in an adult injured trauma population [42] by showing that opiates may reduce the risk for PTSD even after controlling for concurrent pharmacotherapy, even up to 1 year posttrauma.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are in line with previous studies in injured populations that reported associations between morphine prescription and lower levels of PTSD symptoms or lower PTSD incidence in the months following injury [39][40][41][42][43]. Furthermore, they extend these previous findings in an adult injured trauma population [42] by showing that opiates may reduce the risk for PTSD even after controlling for concurrent pharmacotherapy, even up to 1 year posttrauma.…”
Section: Discussionsupporting
confidence: 93%
“…Support for this protective effect was found in post-hoc examinations in prospective studies of trauma survivors. Studies in children with burns [39,40] and traumatic injury [41] found positive associations between morphine dosage during hospitalization and greater decline in PTSD symptoms in the first 6 months posttrauma. In addition, a prospective study of 155 adult injury patients reported that morphine dose within the first 48 h, but not within the first week, was associated with fewer PTSD symptoms at 3 months [42].…”
mentioning
confidence: 98%
“…Nixon et al, 2010;Szczytkowski-Thomson et al, 2013). Administration of morphine following a traumatic event reduces the severity of symptoms and the risk of PTSD development (Bryant et al, 2009;Stoddard et al, 2009). Bryant and collaborators described that acute administration of morphine inhibits the development of fear conditioning following a traumatic injury, suggesting that morphine may be employed as a preventive strategy to reduce the development of PTSD (Bryant et al, 2009).…”
Section: Post-traumatic Stress Disorder (Ptsd)mentioning
confidence: 97%
“…Stoddard and coworkers described a correlation between the morphine usage and PTSD development in young children (1-4 years) admitted to pediatric burn center. Treatment with morphine decreased the development of post-traumatic symptoms, assessed 3-6 months after the burn event (Stoddard et al, 2009). A clinical study by Holbrook and collaborators described that the use of morphine (2-20 mg) in the US military personnel after a combat injury reduces the risk of PTSD development (Holbrook et al, 2010).…”
Section: Post-traumatic Stress Disorder (Ptsd)mentioning
confidence: 99%
“…The first study found a significant correlation between morphine dose in the hospital and decrease in PTSD symptoms over 6 months (Saxe et al, 2001). The second study, which had only 11 completers, found a nonsignificant correlation between morphine dose in the hospital and decrease in PTSD symptoms over 6 months, but a significant correlation between morphine dose and decrease in the arousal cluster of symptoms (Stoddard et al, 2009). Two chart reviews have examined the association between morphine and subsequent PTSD symptoms in adult trauma survivors.…”
Section: Somatic Approachesmentioning
confidence: 99%